(untitled) (Revista de Estudos Orientais, 2021)
Since the late XIX century, China has experienced remarkable economic, cultural, social, and all sort of transformations. In a globalized world, the news about such transformation reaches West and especially Brazil, always intermediated by large and powerful worldwide media groups. In different historical moments during the past 110 years, the literature in Portuguese language, in turn, with a proper touch of Latinity, has presented us such transformations by means of very interesting reports written by Wenceslau de Moraes, Ligia Fagundes Telles, Henfil, João Alves and others. Therefore transformations in China can be learned through eyewitness reports with delicious literary touch.